Extraction of Java Lemongrass (Cymbopogon citratus) Using Microwave-Assisted Hydro Distillation in Pilot Scale: Parametric Study and Modelling - Yeni Variyana; Zuhdi Ma'sum; Donny Satria Bhuana; Mahfud Mahfud (ASEAN Journal of Chemical Engineering, 2023)
This study aims to extract oil from Java lemongrass (Cymbopogon citratus) using the pilot-scale Microwave-Assisted Hydro distillation method (distiller volume 10,000 mL). The operating variables of this research are the extraction time, the microwave power, and the ratio of the mass of the material to the solvent (F/S ratio). The results showed an increase in the yield of lemongrass oil along with the increase in extraction time using the Microwave-Assisted Hydro distillation (MAHD) method, and this trend will continue to occur as microwave heating is selective and volumetric. Thus, there is a tendency to increase yield with increasing power. In general, it follows that the higher the power, the higher the yield. The energy received by the material to be converted into heat has caused the essential oil yield to be more abundant, with the highest yield being obtained at 800 W. The increase in the material to solvent ratio increased the oil yield up to a certain point. However, the yield started declining after the F/S ratio of 0.08 was reached. The first order kinetic model well represents the extraction process at a pilot scale. The pilot scale's oil yield is slightly lower than the laboratory scale MAHD. Compositional analysis of the result suggests that the main components of Java lemongrass oil are Geranial (30.06%), Z-Citral (25.88%), Eugenol (12.88%), and Beta-Myrcene (12.84%).